The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.4209/aaqr.200245
|View full text |Cite
|
Sign up to set email alerts
|

Particle-bound Polycyclic Aromatic Hydrocarbons (pPAHs) in Merida, Mexico

Abstract: This study focuses on the air quality evaluation of Merida, a medium-size city located in the Yucatan Peninsula with a significant population growth in recent years. Particle-bound Polycyclic Aromatic Hydrocarbons (pPAHs) were quantified with a real time sensor during a six-month period during the dry season (October 2017 to March 2018). The pPAHs diurnal and monthly characteristics, as well as their potential sources were determined. The total pPAHs concentrations ranged from 7 ng m -3 to 170 ng m -3 , with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Across recent decades, environmental pollution has been a global problem of great concern due to its detrimental effects on both human health and ecosystems. Anthropogenic activities have discharged a significant amount of pollutants into the environment, and the petroleum sector produces vast amounts of crude oil wastewater with significant pollution ( Mojiri et al, 2019 ; Olajire, 2020 ; Alvarez-Ospina et al, 2021 ). Numerous investigations have shown that toxic substances, such as aliphatic or aromatic hydrocarbons, phenolic compounds, heavy metals, their derivatives, and chemicals used in the de-emulsification process, are always present in crude oil discharge ( Trannum et al, 2011 ; Uzoekwe and Oghosanine, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Across recent decades, environmental pollution has been a global problem of great concern due to its detrimental effects on both human health and ecosystems. Anthropogenic activities have discharged a significant amount of pollutants into the environment, and the petroleum sector produces vast amounts of crude oil wastewater with significant pollution ( Mojiri et al, 2019 ; Olajire, 2020 ; Alvarez-Ospina et al, 2021 ). Numerous investigations have shown that toxic substances, such as aliphatic or aromatic hydrocarbons, phenolic compounds, heavy metals, their derivatives, and chemicals used in the de-emulsification process, are always present in crude oil discharge ( Trannum et al, 2011 ; Uzoekwe and Oghosanine, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to fixed sources of benzene and PAHs, practices such as burning solid wastes, incinerators, and crematories increase levels of carcinogens in the air. Studies have even reported particle-bound PAHs, possibly originating from burning fossil fuels and solid wastes (43).…”
Section: Discussionmentioning
confidence: 99%
“…The ambient PAHs generally existed in the form of vapor phase and particulate phase (Wang et al, 2011b;Zhang et al, 2013;Alvarez-Ospina et al, 2021). Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%